Pemberdayaan Masyarakat Melalui Pemanfaatan Daun Kelor untuk Pupuk Organik Cair Guna Meningkatkan Produktivitas Pertanian Berkelanjutan di Kemiri - Ika Sari Tondang; Fadilla Miftakhul Jannah; Nanda Salsa Dela Nugraini; Deny Maulana Ilham (Lembaga Pengembangan Kinerja Dosen, 2025)
The community service program in Kemiri Village aims to empower farmers through the use of local potential, especially moringa leaves (Moringa oleifera), as raw materials for liquid organic fertilizer (POC). This activity was carried out with a participatory and educational approach that directly involved farmer groups in technical training on making POC through simple fermentation methods using natural ingredients such as moringa leaves, rice washing water, organic waste, and local decomposers. Through this activity, farmers are taught stages ranging from the collection of ingredients, the process of shredding moringa leaves, mixing with complementary ingredients, to the correct fermentation techniques to produce high-quality fertilizer. The training is carried out by field demonstration methods, discussions, and hands-on practice, so that farmers not only gain theoretical knowledge, but also practical skills that can be applied independently. The results show a significant increase in farmers' knowledge, skills, and awareness of the importance of liquid organic fertilizer as an environmentally friendly alternative. In addition, the public's enthusiasm is getting higher after seeing real evidence that the use of POC moringa leaves is able to increase plant growth, crop quality, and reduce dependence on chemical fertilizers which are increasingly expensive and have the potential to damage the soil. This program not only provides economic benefits through the cost efficiency of agricultural production, but also has a positive impact on environmental conservation. This activity is expected to be a model of community empowerment based on local potential that can be replicated in other regions with similar conditions. The success of the program shows that simple innovations that utilize local resources, if managed well, can support sustainable agriculture and food security for rural communities.